Trafficking of women: a study of the relevant law in Malaysia / Noordini Mohd Azahar...[et al.] - Mohd Azahar, Noordini; Johari, Sitti Amyrah; Mohd Ghazali, Fadilla (2006)
Trafficking is a global problem affecting every continent and most countries. It occurs within and across national borders and ranks as one of the most lucrative forms of international crime. Trafficking occurs when involves the movement of people through violence, deception or coercion for the purpose of forced labour, servitude or slavery-like practices. Though it is a serious crime that violates the human rights, there are inadequacy of the laws relating to trafficking. The research project highlights the reasons to inadequacy of the relevant laws in trafficking especially on women trafficking. It set out to examine the punishment to offenders and protection that should be given to victims of trafficking. Through the research, it can be found that there exist inconsistencies in the domestic law and absent of knowledge of human trafficking among society. Thus, Malaysia should create uniformity in domestic laws as well as equipped it with international instruments relating to trafficking.